2015
DOI: 10.1063/1.4926875
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-controlled magnetization in bilayered magnetic films for magnetoelectric memory

Abstract: Articles you may be interested inPhase modulated magnetoelectric delta-E effect sensor for sub-nano tesla magnetic fields Appl. Phys. Lett. 107, 152402 (2015); 10.1063/1.4932575Large E-field tunability of magnetic anisotropy and ferromagnetic resonance frequency of co-sputtered Fe50Co50-B film J. Appl. Phys. 117, 17D702 (2015)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…They found that the magnetic anisotropy was enhanced, while the damping constant was decreased. Our previous work [12,13] investigated how the ME coupling between FeCo films and PMN-PT changed with the introduction of thin magnetic and non-magnetic layers between the film and the substrate. It was found that when thin Metglas (FeSiB) layers were used, that two different magnetisation hysteresis states were achieved at zero applied electric field, depending on whether a large positive or negative electric field was applied [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the magnetic anisotropy was enhanced, while the damping constant was decreased. Our previous work [12,13] investigated how the ME coupling between FeCo films and PMN-PT changed with the introduction of thin magnetic and non-magnetic layers between the film and the substrate. It was found that when thin Metglas (FeSiB) layers were used, that two different magnetisation hysteresis states were achieved at zero applied electric field, depending on whether a large positive or negative electric field was applied [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work [12,13] investigated how the ME coupling between FeCo films and PMN-PT changed with the introduction of thin magnetic and non-magnetic layers between the film and the substrate. It was found that when thin Metglas (FeSiB) layers were used, that two different magnetisation hysteresis states were achieved at zero applied electric field, depending on whether a large positive or negative electric field was applied [13]. For ultra-thin Ti sandwich layers, these layers change the texture within the FeCo films, which increased the switchability of the magnetisation of the FeCo film from ~70% for no Ti layer to ~95% for 8 nm Ti layer [12], thus showing that the morphology of the magnetostrictive layer is important in these structures.…”
Section: Introductionmentioning
confidence: 99%